The feint in football - Vicente, A.; Lopes, H.; Fernando, C.; Almada, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In football training to be able to identify the variables involved in a feint makes it possible to do specific corrections in the action of a player, even if it is a higher level one (but not only), because it allows diagnosing the cause of the error and what can be most useful to train, prescribing exercises that require more emphasis on the improvement of relevant aspects and not the generality of the situation, and even to control the progress that is being achieved through the measurement of the evolution that is happening in the factors trained. So, it`s increased the profits yield because the training is directed to the important aspects in that situation for that player. METHODS We`ve analyzed 276 feint situations through image digitization of videos from high competitive level football matches of clubs and national teams. In the analysis were considered the time of each frame (0.04 seconds) and the relationship established between the stimuli that were provided by the player who made the feint and the response of the opponent. We`ve considered also as a point of reference of minimum reaction time 0.4 seconds. We`ve found in 134 of analyzed situations, those that were not successful, what corrections should be made to avoid the error. In all feints we`ve analyzed the relation between the two players and the corrections that each could make to improve his performance. We`ve also analyzed a number as high as possible of the same situations from the same players, and also in these sets of situations obtain successful as well as missed feints. RESULTS From the 276 analyzed situations we`ve obtained the following distribution: - Total of players analysed 35 - From this 35 players, 26 of them have a sample of 10 feints with an average of 6 succeeded and 4 missed. - From the other 9 players we have a percentage of 12,8 feints from each one being 30 of them missed. We`ve seen that the successful feints were not the ones with shorter execution time, on the contrary, in 76% of them, they were significantly slower that the identical feints from the same player than the feints that were missed. When considering what corrections should be made, was considered that the action of the opponent who made the cut would be the same and found that in 91% of cases if the player action had been slower (taking into account that the opponent`s position would be the same) that he would had naturally succeeded. DISCUSSION The success of a feint is not dependent of the speed with which it is made but in the effect it is possible to obtain in the opponent and the ability of the player who will perform the feint has to wait for the signal that sends to the opponent will make effect before changing his action to what he must to do. The feint, as we set, `is played` in times of decision making and reaction times of both players.